THE INFLUENCE OF STUDENTS' COMPREHENSION ON MARKETING MIX TOWARD THEIR PURCHASE DECISION - HENDRA RIOFITA (Fakultas Ekonomi Universitas Negeri Jakarta, 2018)
The purpose of this study was to determine the effect of student comprehension in translating, interpreting, and extrapolating the concept of the marketing mix on their purchasing decisions. The design of this research is quantitative research. The sample of this study was 59 students of SMK MUhammadiyah 2 Pekanbaru taken using a random sampling technique. Data were collected using a questionnaire and analyzed with the classic assumption test and hypothesis test. The results showed that there was a significant influence between comprehension in translating and interpreting the marketing mix for student purchasing decisions. However, there is no significant effect between comprehensions in extrapolating the marketing mix concept to student purchasing decisions. The results also showed a significant influence between comprehension in translating, interpreting, and extrapolating the marketing mix simultaneously to student purchasing decisions. Keywords: Comprehension, marketing mix, purchase decision.